The Role of Islamic Banks in Improving the Economy through Microfinance During the Covid-19 Pandemic - Fitriani Fitriani; Tuti Anggraini (Penerbit Jurnal Indonesia, 2022)
At the end of 2019 there was a global change due to the corona virus, the virus known as covid-19 first appeared in the city of Wuhan, China. WHO officially announced this respiratory virus as a pandemic in early 2020. This virus causes the death rate to continue to increase both in Indonesia and in the world. This virus affects various sectors, one of the sectors most affected is the economic sector. The virus that brought the community's economy also declined drastically because this outbreak caused a lot of decline in the wheels of community business. Many companies are laying off their employees so that the banking sector, industry and others are affected. The unemployment rate is increasing, and also in the micro-economic sector, many MSMEs have decreased and even went bankrupt. MSME turnover has decreased while MSMEs need capital assistance for their business. To handle and support MSMEs, the role of financial institutions is very much needed. One of the financial institutions that play a role in providing capital for MSMEs is Islamic banking. Because Islamic banking focuses on the real sector. Even so, Islamic banks need a strategy before providing financing so that Islamic banks can maintain financial stability during the pandemic. In this study used descriptive qualitative methods, which this research uses field studies to obtain accurate information by conducting interviews, data analysis and data credibility to get good results. So we know that during the pandemic there are banks providing concessions. And the policy is carried out on each financial institution which has its own policy. Noble from reducing the amount of installment fees and so on.